The effect of reminiscence exercise therapy on functional mobility and psychological well-being among elderly - Fery Agusman Motuho Mendrofa (Universitas Udayana dan Diaspora Taipei Medical University, 2025)
Background: Elderly individuals often experience decline in both physical mobility and psychological well-being. reminiscence exercise therapy (RET) is a novel approach that integrates reminiscence therapy with targeted physical exercises. This study aims to investigate the effect of RET on functional mobility and psychological well-being of elderly residents in a nursing home in Semarang City. Methods: This pre-experimental study used a one-group pretest-posttest design with 36 elderly participants selected through purposive sampling. Functional mobility was assessed using the timed up and go test (TUG) and elderly mobility scale (EMS), while psychological well-being was measured using the geriatric depression scale (GDS-15) and satisfaction with life scale (SWLS). RET was conducted in 6 sessions over 3 weeks. Data were analyzed using the Wilcoxon Signed Rank Test. Results: Significant improvements were observed in all parameters after RET intervention. Mean TUG test time decreased from 15.64 to 12.37 seconds (p=0.001), mean EMS score increased from 14.78 to 17.92 (p=0.001), mean GDS-15 score decreased from 7.36 to 4.83 (p=0.002), and mean SWLS score increased from 18.25 to 23.64 (p=0.001). Conclusion: RET showed potential to improve both functional mobility and psychological well-being in elderly nursing home residents. However, the pre-experimental design limits causal inferences, and further controlled studies are needed.